Calcium intake, serum vitamin D and obesity in children: is there an association? - Kelly Aparecida da Cunha; Elma Izze da Silva Magalhães; Laís Monteiro Rodrigues Loureiro; Luciana Ferreira da Rocha Sant'Ana; Andréia Queiroz Ribeiro; Juliana Farias de Novaes (Revista Paulista de Pediatria, 2015)
OBJECTIVE: To evaluate the association between calcium intake and serum vitamin D levels and childhood obesity by an integrative review. DATA SOURCE: The research was conducted in the databases PubMed/medLine, Science Direct and SciELO with 2001 to 2014 publications. We used the combined terms in English: ''children'' and ''calcium'' or ''children'' and ''vitamin D'' associated with the descriptors: ''obesity'', ''adiposity'' or ''body fat'' for all bases. Cross-sectional and cohort studies, as well as clinical trials, were included. Review articles or those that that have not addressed the association of interest were excluded. DATA SYNTHESIS: Eight articles were part of this review, five of which were related to calcium and three to vitamin D. Most studies had a longitudinal design. The analyzed studies found an association between calcium intake and obesity, especially when age and sex were considered. Inverse relationship between serum vitamin D and measures of adiposity in children has been observed and this association was influenced by the sex of the patient and by the seasons of the year. CONCLUSIONS: The studies reviewed showed an association between calcium and vitamin D with childhood obesity. Considering the possible protective effect of these micronutrients in relation to childhood obesity, preventive public health actions should be designed, with emphasis on nutritional education.